Double Morita–Baylis–Hillman (MBH) strategy; an intermolecular and a chemo selective intramolecular MBH reactions for 5/6 substituted, functionalized piperidine unit. Issue 2 (14th January 2016) - Bharadwaj, Kishor Chandra; Tiwari, Dharmendra Kumar
Abstract: A novel approach utilizing dual Morita–Baylis–Hillman (MBH) reactions in form of intermolecular and a chemo selective intramolecular version, has been developed. With three electrophilic and a nucleophilic site in precursor, selective condition for intramolecular MBH reaction has been optimized. Role of water was found to be crucial. The dual strategy was applicable for synthesis of a variety of medicinally and synthetically important piperidine unit whose 5/6 atoms of ring were substituted, featuring a stereo defined trisubstituted olefin, a Michael acceptor (with a methylene moiety), trivalent nitrogen and a tertiary alcohol. Graphical abstract: